Overstretching Expectations May Endanger the Success of the “Millennium Surgery” - Bender, Alwina; Damm, Philipp; Hommel, Hagen; Duda, Georg N. (Frontiers in Bioengineering and Biotechnology, 2022)
Total hip arthroplasty (THA) is an extremely successful strategy for treating. Patient expectations, however, have increased, and if not properly guided by surgeons they expect today next to pain-free restoration of the joint a fast return to work and sport. While revision rates after THA increase also in younger patients, knowledge on musculoskeletal loads remains still sparse, and current recommendations on postoperative rehabilitation are based on expert opinions only. The aim of this study was to unravel biomechanical contact conditions in ‘working age’ (<60 y, 53.5 ± 3.0 y) and ‘retirement age’ (>60 y, 67.7 ± 8.6 y) patients during activities recommended post-THA. We hypothesized that ‘working age’ patients would show substantially increased hip contact loads compared to older patients. In-vivo joint contact forces (Fres) and torsion torque (Mtors), reflecting the main contact load situation, experienced during activities of daily living and sportive activities are measured in a unique group of 16 patients with instrumented THA. We summarize patient activities and sport recommendations after THA mentioned within the literature using PubMed (without claim of completeness). Measurements show that younger ‘working age’ patients experienced significant (p = 0.050) increased Mtors (21.52 ± 9.11 Nm) than older ‘retirement age’ patients (13.99 ± 7.89 Nm) by walking. Bowling as a recommended low-impact sport is associated with Fres up to 5436 N and Mtors up to 108 Nm in the ‘working age’ group, which is higher than Fres (5276 N) and Mtors (71 Nm) at high-impact soccer. Based on our results, age proved to be a discriminator in joint loading with ‘working age’ patients presenting with increased loads compared to ‘retirement age’ patients, already during daily activities. Today’s patient recommendations lead to further increased joint loadings. If THA cannot be delayed in a patient, we propose counselling patients on a carefully considered return to sports, focusing on low-impact activities, as indicated hereby. The findings from this work illustrate the need to provide critical feedback to patient expectations when returning to work and sportive activities. Patients returning to more intensive sport activities should be carefully monitored and advised to avoid as much overloading as possible.